Innovation ecosystems for meeting sustainable development goals: The evolving roles of multinational enterprises - Nylund, Petra A.; Brem, Alexander; Agarwal, Nivedita (Journal of Cleaner Production, 2021)
Meeting the United Nations sustainable development goals (SDGs) will require breakthrough innovations in a number of areas. Multinational enterprises (MNEs) can contribute to these goals by fomenting innovation considering the coevolution of responsible research and innovation (RRI) with the maturity of innovation ecosystems. Therefore, a conceptual model of the roles of multinational enterprises contingent on the evolutionary phases of a firm and the ecosystem in which it is embedded is derived. These MNE roles and RRI activities in SDG-oriented innovation ecosystems are explored through case examples of specific multinationals. Based on different archetypes of innovation ecosystems and RRI maturity levels, the identified roles include secretive innovators, builders, theater directors, platform leaders, dominators, and amplifiers. More responsible enterprises are found to support the SDGs through platform leadership and by amplifying the sustainable innovations of other ecosystem participants, whereas less responsible firms innovate internally and achieve less sustainable results.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Innovation ecosystems; Multinational enterprise; Responsible research and innovation; Sustainability management; Sustainable development goals